“Sorry! I left it at home”: examining rape humor’s potential role in rape culture - Strain, Megan (Kansas State University, 2014)
The current studies examine two types of rape humor to determine whether there are differences in individuals’ evaluations and understanding of each. Reinforcing rape humor is that which contributes to the normalization of rape, while subversive humor challenges it. Across two studies, I compared these types of humor to determine if individuals’ evaluations (i.e., as funny, offensive, etc.) and understanding differed between types (and compared to neutral humor), as well as how individual difference variables may moderate those effects. Results suggest that while there is variation in individuals’ understanding of subversive humor depending on the way in which they are asked to express their understanding, subversive humor evokes more positive evaluations than reinforcing rape humor, as expected. Additionally, reinforcing rape humor also evoked variation in understanding, which was related to participants’ evaluations of the humor, and selected individual differences. Examining these research questions provides insight into an issue that has become increasingly important in the United States, and may also inform us about the potential role of humor in contributing to the national discussion on this issue. Thus, although some have suggested that rape humor is never appropriate, these studies suggest that there is potential for humor to be an effective tool in working toward diminishing rape culture.
Keywords: Rape humor; Humor perceptions; Humor understanding; Gender; Social Psychology (0451)